Reputation, Competition, and Entry in Procurement - Giancarlo Spagnolo (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2012)
Based on my recent work with several co-authors this paper explores the relationship between discretion, reputation, competition and entry in procurement markets. I focus especially on public procurement, which is highly regulated for accountability and trade reasons. In Europe regulation constrains the use of past performance information to select contractors while in the US its use is encouraged. I present some novel evidence on the benefits of allowing buyers to use reputational indicators based on past performance and discuss the complementary roles of discretion and restricted competition in reinforcing relational/reputational forces, both in theory and in a new empirical study on the effects restricted rather than open auctions. I conclude reporting preliminary results form a laboratory experiment showing that reputational mechanisms can be designed to stimulate rather than hindering new entry.
Keywords: H57; L14; L15; L24; 330; Accountability; Discretion; Entry; Incomplete contracts; Limited enforcement; Past performance; Procurement; Quality; Relational contracts; Reputation; Restricted auctions